The influence of organizational values on the management styles of small firms - Gosendo, Eliana Elisabete Moreira; Torres, Cláudio Vaz (Paidéia (Ribeirão Preto), 2010)
There is a scarcity of studies addressing Psychology and Social Work in the context of small firms and few addressing populations with low educational level. This study aimed to identify the hierarchy of organizational values and management styles and to investigate the influence of organizational values on management styles. The sample was composed of employees from 30 firms. A method adapted to individuals with low educational level was used in data collection. The results indicate that the organizational value "Control" and management style "Task-oriented" were the most perceived by employees. The values "Autonomy" and "Well-Being" were the best predictors of the "Relationship-oriented" management style. The value "Conformity" is the only predictor of the management style "Task-oriented" and the value "Autonomy" is the best predictor of the management style "Situational".